Relativistic Hartree-Fock and Dirac-Fock atomic structure and radiative parameter calculations in nine-times ionized xenon (Xe X). (April 2019) - Motoumba, E. Bokamba; Yoca, S. Enzonga; Palmeri, P.; Quinet, P.
Highlights: A theoretical investigation of the atomic structure of Xe X is presented for the first time. Spectroscopic designations have been determined for all the experimentally known levels. A new set of radiative data for 92 Xe X lines between 110 and 164 Å is reported. Abstract: A new set of oscillator strengths and transition probabilities is reported for 92 radiative transitions of nine-times ionized xenon, Xe X, in the extreme ultraviolet region from 110 to 164 Å. They have been obtained by two different theoretical approaches, i.e. the pseudo-relativistic Hartree-Fock (HFR) and the fully relativistic multiconfiguration Dirac-Hartree-Fock (MCDHF) methods, which allowed us to estimate the precision of the final results. The eigenvector compositions are also given for the first time for all the experimentally known energy levels in Xe X.